Inhibition of leucocyte migration as an index of rejection in renal transplant recipients - Richmond, D. E. (1973)
In a blind study, the peripheral blood leucocytes of fifteen recipients of cadaver kidney homografts have been checked at regular intervals for migration inhibition in the presence of antigen derived from donor spleen. Six of seven episodes of definite acute rejection were preceded or accompanied by migration inhibition, and four of seven probable acute rejection crisis were similarly accompanied by inhibition. No false positive tests were observed. The technique may be a useful adjunct to present methods of diagnosing acute homograft rejection.